The role of land values in land policies: The case of Turkish land readjustment - Yilmaz, Ahmet; Bilim, Nazim Serdar (ELSEVIER SCI LTD, 2024)
The many problems in cities increase the need for effective land policies. Land values are at the core of land policy frameworks as they shape the implementation strategies of local governments, their effectiveness, and the consequences for individuals and society. The aim of this paper is to examine how land values within the land policy framework influence land policy objectives, with a particular focus on land readjustment. More specifically, through a three-step research process, we examine: (1) the current problems and potential improvements of Turkish area-based land readjustment through an analytical framework; (2) the potential impact of a specific policy intervention involving the provision of land values in land readjustment on land development objectives through a multiple case study approach; and (3) the broader implications of a new value-based land readjustment as a land policy instrument. The results suggest that land readjustment, by incorporating valuation, could provide better land development by enabling the acquisition and construction of public and infrastructure areas, has the potential to address the trade-offs faced by local governments, put fiscal decentralization into practice, and contribute to the development of legitimacy, effectiveness, efficiency, and equity in public land development strategies and land management.
Keywords: Valuation; Land Policy; Value Capture; Land Readjustment; FRAMEWORK; Environmental Sciences & Ecology